Internal Marketing Practices and Customer Orientation of Employees in Nigeria Banking Sector - Yusuf, Gafar Olanrewaju; Sukati, Inda; Andenyang, Ifu (International Review of Management and Marketing, 2016)
The present paper is primarily aimed at determining the influence of internal marketing on customer orientation of Nigerian banks' employees. It specifically seeks to determine the impact of internal marketing practices on customer orientation of Nigerian banks' employees while investigating the mediating impact of personality factors and job satisfaction in the relationship between internal marketing and employees' customer orientation in the Nigeria banking industry. The paper adopted a survey and this was conducted among the existing twenty-one (21) Nigerian banks that operate in Lagos State, south western part of Nigeria. The study selected four branches of each of these banks from the following key business centers in the state: Victoria Island, Ikeja, Ikoyi, Apapa, Idumota, Yaba, and of course Isolo/Oshodi. The population of this paper comprised 687 management staff and 2,326 frontline employees drawn from the four branches so selected. Using simple random sampling technique, the paper selected 253 management staff and 341 frontline employees as sample size. The relevant data were collected from primary source, using structured questionnaire. Our findings showed that internal marketing has a significant relationship with customer orientation while personality trait factors and job satisfaction constructs were found to mediate significantly the influence of internal marketing practices on customer orientation behavior of banking employees in Nigeria. The paper thus, recommended that management of banking industry in Nigeria should improve on internal marketing to be able to lower the tendency of adverse effect from poor personality trait factors and low job satisfaction on customer orientation behaviors of the employees. Keywords: Internal Marketing, Customer Orientation, Personality Traits, Job Satisfaction JEL Classifications: C12, G21, M31